Blockchain and Self-Sovereign Identity: A Healthcare Use Case - Honório da Silva, Matheus Lázaro; Velasco, Gislainy; Pimentel Vaz, Noeli Antônia; Martins, Matheus Brito; Ribeiro Gonçalves Silva, Pedro Moraes; Carvalho, Sergio T. (Workshop em Blockchain: Teoria, Tecnologias e Aplicações (WBlockchain); 2025: Anais do VIII Workshop em Blockchain: Teoria, Tecnologias e AplicaçõesDO - 10.5753/wblockchain.2025.9506, 2025)
This paper proposes an architecture based on permissioned blockchain and self-sovereign digital identity (SSI) to address demands related to privacy, traceability, and decentralized governance in healthcare. Decentralized Identifiers (DIDs) and Verifiable Credentials (VCs) give patients greater control over their clinical data. The hybrid on-chain/off-chain approach enables the recording of immutable events and the management of credential issuance and verification. A functional prototype, SSISH (Self-Sovereign Identity System for Healthcare), demonstrates secure and interoperable workflows for examinations, diagnoses, and treatments. Preliminary results indicate increased transparency and reliability in information exchange, although further evaluation of scalability and governance in real-world environments remains necessary.